2013
DOI: 10.15376/biores.8.3.3505-3517
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Lignin-Based Anion Exchangers and their Utilization for Nitrate Removal

Abstract: Lignin-based anion exchangers (L-AE) were prepared by reacting lignin with epichlorohydrin and triethylamine in the presence of N,Ndimethylformamide and a catalyst. A multi-factor and multi-level orthogonal design of experiment was carried out in order to obtain the optimal conditions for the preparation of lignin-based anion exchangers. The optimized parameters including the dosages of catalysts, the amounts of triethylamine, graft reaction time, and the graft reaction temperature were defined. Data of nitrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Compared with the original sample, the cationic cellulose has a new peak at 1491 cm −1 (C N, 1000-1400 cm −1 ), which assign to the quaternary ammonium group. In addition, a prominent peak at 1479 cm −1 was observed, which assign to methylene bending mode and methyl groups of the cationic substituent (Wang, Bo, Liu, Yang, & Zhao, 2013). These FTIR results indicate that the original cellulose was successfully modified into cationic cellulose.…”
Section: Ft-ir Analysismentioning
confidence: 76%
“…Compared with the original sample, the cationic cellulose has a new peak at 1491 cm −1 (C N, 1000-1400 cm −1 ), which assign to the quaternary ammonium group. In addition, a prominent peak at 1479 cm −1 was observed, which assign to methylene bending mode and methyl groups of the cationic substituent (Wang, Bo, Liu, Yang, & Zhao, 2013). These FTIR results indicate that the original cellulose was successfully modified into cationic cellulose.…”
Section: Ft-ir Analysismentioning
confidence: 76%
“…Also, the trend of decreasing potential of both biomass and sorbent with increasing pH (from 3 to 11) can be attributed to the influence of pH-dependent functional groups of biomass with negative zeta potential (OH group of cellulose and OCH 3 group of lignin skeleton). These groups show a higher negative charge with increasing pH, which results in a decrease in the positive charge of the tested samples [56]. Certainly, the analysis of the PZC confirmed the effectiveness of the biomass chemical modification by introducing quaternary ammonium groups that contribute to a more positive potential of the sorbent.…”
Section: Reaction Path Of the Cationic Lvsat-chmac Sorbent Synthesis:...mentioning
confidence: 66%
“…The L-Cu nanocomposite displayed a noticeable peak at 14.27° for lignin and 36.4°, 42.4°, 61.3°, 73.5°, and 77.4° diffraction peaks corresponding to Cu 2 O NPs, these diffraction peaks indicated that due to strong capping treatment of Cu 2 O NPs with lignin, a new phase was formed, appreciably even though a very small amount of the Cu 2 O powder was used for the synthesis of L-Cu. Cu 2 O NPs and alkaline lignin are positively charged at neutral pH [35] . Thus, hydrophobic interactions between lignin and Cu 2 O played an important role in the formation of stable L-Cu.…”
Section: Resultsmentioning
confidence: 99%